The prognostic potential of fragmented CK18 serum levels in HCC patients reflecting disease progression and overall hepatocyte damage - Eguchi, Akiko; Iwasa, Motoh; Tamai, Yasuyuki; Yamada, Minori; Okuno, Koji; Shigefuku, Ryuta; Yoshikawa, Kyoko; Tempaku, Mina; Sakaguchi, Koji; Tanaka, Hideaki; Sugimoto, Kazushi; Kobayashi, Yoshinao; et al. (Frontiers in Oncology, 2022)
[Background] Fragmented cytokeratin 18 (fCK18) is released from damaged hepatocytes undergoing apoptosis and is recognized as a liver condition biomarker. We have developed a highly sensitive serum fCK18 CLEIA and reported that serum levels of this caspase-derived protein were significantly associated with hepatocyte ballooning, thus assisting in the accurate diagnosis of nonalcoholic steatohepatitis (NASH). We aim to investigate serum fCK18 levels in a variety of chronic liver diseases and to explore its potential as a prognostic marker of survival in hepatocellular carcinoma (HCC) patients. [Methods] Serum fCK18 levels were measured using a highly sensitive CLEIA in 497 chronic liver disease patients (297 outpatients and 200 hospitalized with HCC). [Results] In 497 chronic liver disease patients, serum fCK18 levels were significantly correlated with overall liver condition, including ALT, FIB-4 index and albumin-bilirubin (ALBI) score and were significantly increased in patients with HCC. In 200 HCC patients, serum fCK18 levels were significantly correlated with alpha-fetoprotein (AFP) and des-gamma-carboxy prothrombin (DCP), and were significantly associated with HCC stage, whereas FIB-4 index and ALBI score were not changed based on HCC stage. The Survival group had significantly lower levels of serum fCK18, AFP, DCP, FIB-4 index and ALBI score. A ROC analysis yield area under the curve (AUC) value of 0.728 for serum fCK18 is a significantly high value when compared to AUC measurements for other factors. Notably, AUROC values for serum fCK18 levels were constant in the short- and long-term by time-dependent ROC analysis for the prediction of HCC patient survival. HCC patients with serum fCK18 measured at < 1.15 ng/mL, AFP < 7.7 ng/mL, DCP < 133 mAU/mL, ALBI score < -2.97 or FIB-4 index < 6.4 had significantly longer rates of survival when compared to patients with values exceeding these thresholds. Serum fCK18 (HR, 3.5; P < 0.0001), DCP (HR, 3.2; P < 0.0001) and Barcelona Clinic Liver Cancer (BCLC) (HR, 2.4; P = 0.001) values were independent predictors of patient survival. [Conclusion] Serum fCK18 levels reflect overall liver function, the level of liver fibrosis and the progression of HCC, and are a potential predictor of survival in HCC patients.